Wednesday

April 23, 2014

April 23, 2014

Posted by **dee** on Friday, December 22, 2006 at 6:13am.

If you mean

(3x-5)/6= (7x+4)/4 , then

12 x - 20 = 42 x + 24

and you can take it from there.

If you mean 3x - 5/6 = 7x + 4/4,

then the answer will be different.

Please use parentheses to clarify ambiguous algebraic statements such as the one you typed.

**Related Questions**

Math - Can someone please check my answers below for accurateness? The ...

Algebra - I got a couple I want to check my work : Both are Solve using the ...

Math - Simplify. (5x2 + 3x - 7) - (x2 - 7x + 4) Simplify. (5x^2 + 3x - 7) - (x^2...

Math - I have 4 math problems that need to be solved by using factoring. I am ...

Algebra - Checking two problems : 1. x^2-7x+12 / x^2-16 = (x-3)(x-4) / (x-4)(x+4...

Math - 5/3x+1/3x=3x+40/3+7/3x 3(5/3x+1/3x)=3(3x+40/3+7/3x) 7x+1x=9x+9+7x 7x=17x+...

algebra - solve 4^3x-4=32^x+2 Please help! Do you mean 4^(3x) -4 = 32^x +2 ? yes...

Math - Write these in factored form? 12 +6x x+x+x+6 x^2 + 3x x^2 + 4x +3 Combine...

algebra - Solve the equations symbolically. 3x+7/4 + 3x-7/5 =-8/5 6(7x-1)+5=24+...

Please check Algebra - Please take a look at my work and let me know if I made ...